Analisis Penggunaan Biaya Input Produksi Usahatani Sistem Intensifikasi Dan DIversifikasi Masa Covid-19 Di Atu Lintang Kabupaten Aceh Tengah - Khairun Nisa Waleny; Widyawati Widyawati; Teuku Fauzi (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
The implementation of agricultural intensification and diversification in Atu Lintang is an effort by farmers to maintain economic stability during the COVID-19 pandemic. The use of costs incurred for production inputs must be considered. This study aims to compare the total expenditure on input costs for intensification and diversification farming in Atu Lintang, as well as to analyze the feasibility of the two farms to be run during the COVID-19 pandemic in Atu Lintang. The research method is thetechnique Snowball Sampling. The method of analysis using descriptive analysis, income analysis using the equation =TR-TC and feasibility analysis using the B/C ratio. The results showed that the average total sample farmers spent on chili intensification production input costs was Rp. 11,763,033/planting season and received an income of Rp. 58,800,000/planting season, so that the net income of farmers was Rp. 47,036,967/planting season. Meanwhile, the costs incurred for procuring diversified inputs amounted to Rp. 6,590,229/planting season and received an income of Rp. 7,837,500/planting season, so that the net income of farmers was Rp. 1,247,271/planting season. Intensification farming is feasible with a B/C ratio = 4. Likewise, diversification farming is also easible because the B/C ratio = 1.2. Conclusion accept Ho and reject Ha . The most profitable farming run during the COVID-19 pandemic in Atu Lintang is intensification because the B/C ratio is higher.